Clinical evidence of growth hormone for infertile women with diminished ovarian reserve undergoing IVF: a systematic review and meta-analysis - Lin, Guangyao; Zhong, Xiufang; Li, Shengnan; Xu, Lianwei (Frontiers in Endocrinology, 2023)
Objective To appraise the current randomized clinical trials (RCTs) for evidence of the association of growth hormone (GH) with improved outcomes in infertile women with diminished ovarian reserve (DOR) undergoing in vitro fertilization (IVF). Methods Relevant RCTs published in Chinese or English were identified through a comprehensive search of nine databases from the period of database inception to April 20, 2023. We included trials investigating adjuvant GH during ovarian stimulation and reported the subsequent outcomes. The group with adjuvant GH treatment and the group without adjuvant GH treatment were set up as the trial and control groups, respectively. The quality of RCTs was measured according to the Cochrane Collaboration Handbook. Results Of the 579 studies initially identified, 10 RCTs comprising 852 infertile women with DOR were included. The GH dose of individual trials ranged between 3 and 5 IU/day. Overall, we judged the trials to be at high risk of bias in the blinding domain. Pooled results showed that GH was associated with an increased clinical pregnancy rate (RR = 1.63, 95%CI [1.31, 2.03], p < 0.0001) and a greater number of oocytes retrieved (MD = 0.91, 95%CI [0.47, 1.35], p < 0.0001). Favorable associations were also observed when ovarian stimulation was combined with GH therapy for improving the optimal embryos rate (RR = 1.84, 95%CI [1.30, 2.59], p = 0.0005) and the number of optimal embryos (MD = 0.28, 95%CI [0.08, 0.48], p = 0.005) along with reducing the cycle cancellation rate (RR = 0.46, 95%CI [0.24, 0.89], p = 0.02). Moreover, GH resulted in an increase in the fertilization rate (RR = 1.33, 95%CI [1.18, 1.50], p < 0.00001) and the embryo implantation rate (RR = 1.56, 95%CI [1.21, 2.01], p = 0.0006). In addition, there was a significant enhancement in estradiol levels (SMD = 1.18, 95%CI [0.46, 1.91], p = 0.001) and endometrial thickness (MD = 0.75, 95%CI [0.41, 1.09], p < 0.0001) on the day of hCG. With regard to the total number of days and total dose of gonadotrophins used, GH treatment was correlated with shorter days (MD = -0.26, 95%CI [-0.46, -0.06], p = 0.01) and lower dose (MD = -460.97, 95%CI [-617.20, -304.73], p < 0.00001) of gonadotrophins applied during ovarian stimulation. Furthermore, GH in conjunction with the GnRH antagonist protocol was more conducive to improving the number of oocytes retrieved when compared with the GnRH agonist protocol (p < 0.0001). Moreover, a notable association was also seen in IVF combined with GH more than or equal to 4.5 IU/day to increase the number of optimal embryos and estradiol levels on the day of hCG (p < 0.05). Conclusion For infertile women with DOR undergoing IVF, adjuvant treatment with GH during ovarian stimulation protocols showed better clinical outcomes, shorter days and lower dosages of gonadotrophin required. Furthermore, well-designed RCTs are needed to verify our results in the future. Systematic review registration https://www.crd.york.ac.uk PROSPERO (CRD42023421739)